Association Between Body Mass Index (BMI) and Occurrence of Esophageal Cancer - Mehwish Jabeen, Ghulam Haider, Sana Sehar, Berkha Rani, Sana Nasir, Muhammad Owais Khan, Sona Devi, Shumaila Nawaz Khan (Pakistan Journal of Medical & Health Sciences, 2024)
Aim: Esophageal cancer, one of the leading causes of cancer deaths globally, has been linked to body mass index (BMI). Studies have shown varying associations between BMI and different subtypes of esophageal cancer, namely adenocarcinoma and squamous cell carcinoma. However, there is limited literature from Pakistan on this topic. This study aims to investigate the association between BMI and the occurrence of esophageal cancer in a Pakistani population. Methods: A prospective observational study was conducted at the Oncology Department of Jinnah Postgraduate Medical Center, Pakistan. Participants included patients over 18 years old with suspected adenocarcinoma or squamous carcinoma of the esophagus. The study utilized a non-probability consecutive sampling technique, and data was collected using a predefined proforma. The association between BMI and types of esophageal carcinoma was analyzed using Chi-square tests. Results: The study found a statistically significant relationship between increasing BMI and the risk of developing esophageal adenocarcinoma. Conversely, a lower BMI was associated with a higher risk of squamous cell carcinoma. These findings align with existing literature that suggests different BMI associations with esophageal cancer subtypes. Conclusion: This study underscores the distinct relationships between BMI and different types of esophageal cancer. It highlights the importance of considering BMI as a factor in the risk assessment for esophageal cancer, particularly in the Pakistani population. Keywords: Esophageal Cancer, Body Mass Index (BMI), Adenocarcinoma, Squamous Cell Carcinoma